The requirements and importance of intercultural communication Competence in the 21st century - Sarwari, Abdul Qahar; Hamedi, Mohd Adnan; Mohamad Saleeh, Rahamad; Mohammad Nubli, Abdul Wahab (SAGE Publications Inc., 2024)
This systematic review assessed the requirements and importance of intercultural communication competence (ICC) in human life in the 21st Century, focusing on its practical aspects and elements. The results reported in the current study are from a review of 45 papers published from 2000 to 2023 in 16 different Web of Science and SCOPUS-indexed journals. To record and select the related and required papers, an online search was done using two key terms, “intercultural competence” and “intercultural communication competence,” and through the use of WoS and SCOPUS databases. A total of 87 items were recorded from the online search, and after a quick review of all records, 45 papers were selected and reviewed thoroughly. Based on the results from the reviewed papers, ICC is one of the main requirements of human life in today’s globalized world, especially in modern education and international business. Findings indicate that the absence of ICC is a crucial reason for failure in many modern professionals. Based on the results, cultural awareness and intercultural sensitivity, language proficiency, empathy, flexibility, and some other traits and skills are among the main components of ICC. The results indicate that staying and studying in multicultural environments, participating in cultural programs, observing felling and emotions, flexibility, and other factors, discussed in the current work, help individuals improve their ICC.